Corticosteroids and infliximab impair the performance of interferon-γ release assays used for diagnosis of latent tuberculosis. Issue 10 (3rd February 2017) - Edwards, Alexander; Gao, Yifang; Allan, Raymond N; Ball, Darran; de Graaf, Hans; Coelho, Tracy; Clifford, Vanessa; Curtis, Nigel; Williams, Anthony; Faust, Saul N; Mansour, Salah; Marshall, Ben; et al.
Abstract : The impact of immunosuppression on interferon-γ release assays and novel cytokine biomarkers of TB infection, mycobacteria-specific IL-2, IP-10 and TNF-α responses was investigated in an ex vivo model. Cytokine responses in standard QuantiFERON-TB Gold in-Tube (QFT-GIT) assays were compared with duplicate assays containing dexamethasone or infliximab. Dexamethasone converted QFT-GIT results from positive to negative in 30% of participants. Antigen-stimulated interferon-γ, IL-2 and TNF-α responses were markedly reduced, but IP-10 responses were preserved. Infliximab caused QFT-GIT result conversion in up to 30% of participants and substantial reductions in all cytokine responses. Therefore, corticosteroids and anti-TNF-α agents significantly impair interferon-γ release assay performance. IP-10 may be a more robust TB biomarker than interferon-γ in patients receiving corticosteroids.